Chagas Disease mortality in Northeastern Brazil: Trends and spatial analysis (2012–2023) (Research, Society and Development, 2025)
Aim: To investigate the spatial patterns and temporal trends of Chagas disease (CD)-related mortality in northeastern Brazil and to evaluate its association with socioeconomic and demographic risk factors. Methods: This ecological study used data from the Brazilian Mortality Information System (2012–2023). Temporal trends were analyzed using Joinpoint software, and spatial distribution was assessed via Moran’s I statistic. The rationale for focusing on northeastern Brazil stems from its historically high endemicity, socioeconomic vulnerabilities, and persistent health inequities, making it a priority area for epidemiological surveillance and health planning. Results: A total of 11,934 CD-related deaths were recorded, predominantly in males (58.2%), individuals over 50 years (88.4%), those of brown ethnicity (59.4%), and with low schooling (63%). Overall, mortality rates declined (AAPC = -1.54; 95% CI: -2.1 to -1.1), though trends varied across states. No global spatial autocorrelation was detected (Moran’s I = 0.4; p = 0.35), but local analysis (LISA) identified Bahia, Alagoas, and Pernambuco as hotspots. Conclusion: CD-related mortality in northeastern Brazil shows a modest declining trend but persists with significant regional disparities linked to socioeconomic factors. This study highlights the urgent need for region-specific public health strategies and targeted interventions.